1993
DOI: 10.1095/biolreprod48.6.1360
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins Alter the Abundance of Messenger Ribonucleic Acid for Steroidogenic Enzymes in Cultured Porcine Granulosa Cells1

Abstract: The effects of prostaglandin F2 alpha (PGF2 alpha) and prostaglandin E2 (PGE2) on the accumulation of progesterone and mRNA for the steroidogenic enzymes 3 beta-hydroxysteroid dehydrogenase (3 beta-HSD) and cytochrome P450 side-chain cleavage (P450scc) were determined in luteinized granulosa cells. These cells were aspirated from 3-5-mm follicles of prepubertal pigs and cultured 48 h with 10% serum and then 48 h under serum-free conditions. Cells were then incubated with medium (control), ovine LH (20 ng/ml), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…PGE 2 has been involved in the maintenance of the CL during early pregnancy when progesterone secretion from the CL is essential for the establishment and maintenance of pregnancy (Christenson et al 1994). According to Grimes et al (1993), PGE 2 enhances progesterone synthesis via cAMP stimulation, as well as the expression of the genes for both steroidogenic enzymes 3 -hydroxysteroid dehydrogenase (3 -HSD) and mitochondrial cytochrome P450 scc (Li et al 1993). Our in vitro study demonstrated direct PGE 2 -receptor-mediated effects in CL of pseudopregnant rabbits only in the early luteal phase.…”
Section: Discussionmentioning
confidence: 57%
“…PGE 2 has been involved in the maintenance of the CL during early pregnancy when progesterone secretion from the CL is essential for the establishment and maintenance of pregnancy (Christenson et al 1994). According to Grimes et al (1993), PGE 2 enhances progesterone synthesis via cAMP stimulation, as well as the expression of the genes for both steroidogenic enzymes 3 -hydroxysteroid dehydrogenase (3 -HSD) and mitochondrial cytochrome P450 scc (Li et al 1993). Our in vitro study demonstrated direct PGE 2 -receptor-mediated effects in CL of pseudopregnant rabbits only in the early luteal phase.…”
Section: Discussionmentioning
confidence: 57%
“…It should, however, be noted that the P450scc mRNA signal was undetectable in stage IV CL, indicating that there is complete loss during regression. Further, in luteinized porcine granulosa cells, LH and cAMP elevate P450scc mRNA abundance, and PGF 2 , treatment reduces this stimulation in a time-and dose-dependent manner [8], demonstrating that regression interferes with the expression of this gene.…”
Section: Discussionmentioning
confidence: 92%
“…These messages decline during luteal regression in vivo in the ewe [6] and cow [7] and in luteinized porcine granulosa cells in culture treated with prostaglandin F 2 Q (PGF 2 .) [8]. However, it is of interest to note that immunohistochemically detectable 3HSD protein remains present in a substantial portion of the cells of both the ovine and bovine CL during the late stages of regression [9] in spite of the dramatic reduction in detectable message [7], implying a relatively long half-life of steroidogenic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors for 3β-HSD expression in the ovaries are progesterone and androgen, and the connection between the receptors for these steroids and the expression of 3β-HSD has been found at some stages in the corpus luteum development [9395]. Prostaglandin F2α and E2 have been observed to affect the accumulation of progesterone and 3β-HSD mRNA in porcine luteinised granulosa cells [96]. In the corpus luteum , the mitochondrial 3β-HSD is especially important for steroidogenesis because of the co-localization with P450scc [97].…”
Section: 3β-hsd In Other Tissuesmentioning
confidence: 99%